'Women in industry are not meant to be weightlifters': Gender and the Australian industrial workplace safety film. Issue 3 (2nd September 2022) - Russell, Grace C.
ABSTRACT: 'Utilitarian' films - those not for the purposes of art or entertainment - include instructional films addressing workplace safety. Large quantities of these were made in Australia between WW2 and the advent of video and were viewed by many workers in different industries. Their content, social significance and relationship to a wider dispositif of media and labour is therefore a fertile source of information about how work was performed and how it was discursively conceptualised. We can glean information from these films about the presumed class, proclivities, and attitudes that Australian workers were assumed to have. Their address is also gendered, almost exclusively targeting men. In analysing one unusual workplace safety film targeted at women workers, Don't Be Scalped (R.D. Hansen, 1960 Fortune films and the NSW Department of Labour and Industry), aspects of working-class male subjectivity commonly spoken to in workplace safety films are thrown into relief. This article examines how gendered address in industrial safety films constructs and perpetuates gendered inequalities in broader discourses about health, danger and industrial labour. Don't Be Scalped illustrates how gender difference is one way this form of utilitarian text polices and normalises attitudes to safety through targeted and specific forms of subjectification.